Smart fabric sensors and e-textile technologies: a review - Castano, Lina M; Flatau, Alison B (Smart materials and structures, 2014)
This paper provides a review of recent developments in the rapidly changing and advancing field of smart fabric sensor and electronic textile technologies. It summarizes the basic principles and approaches employed when building fabric sensors as well as the most commonly used materials and techniques used in electronic textiles. This paper shows that sensing functionality can be created by intrinsic and extrinsic modifications to textile substrates depending on the level of integration into the fabric platform. The current work demonstrates that fabric sensors can be tailored to measure force, pressure, chemicals, humidity and temperature variations. Materials, connectors, fabric circuits, interconnects, encapsulation and fabrication methods associated with fabric technologies prove to be customizable and versatile but less robust than their conventional electronics counterparts. The findings of this survey suggest that a complete smart fabric system is possible through the integration of the different types of textile based functional elements. This work intends to be a starting point for standardization of smart fabric sensing techniques and e-textile fabrication methods.